FRI0350 The IFN Biomarker Siglec1 Indicates Extraglandular Manifestation in Primary Sjögren's Syndrome. (15th July 2016) - Rose, T.; Szelinski, F.; Burmester, G.; Hiepe, F.; Biesen, R.; Dörner, T.
Abstract : Background: Over the last decades evidence of an activated type I interferon (IFN) system in the pathogenesis of different autoimmune diseases such as Sjögren's Syndrome (pSS) (1, 2) has emerged to an extent, that anti-IFN therapies are tested in clinical trials.(3) On the other hand, IFN biomarkers are missing in clinical practice, although those biomarkers might be useful to guide clinical decision making or as pharmacodynamic marker.(4) Objectives: To investigate the IFN biomarkers Sialic acid-binding Ig-like lectin 1 (SIGLEC1) and IFNγ-inducible protein-10 (IP-10) in patients with pSS. Methods: 23 patients with pSS were included. Disease activity was obtained by EULAR Sjögren's syndrome disease activity index (ESSDAI). SIGLEC1 expression on monocytes was analyzed by flow cytometry. IP-10 was determined by Bioplex human Cytokine 27-plex kit. The correlation analysis was performed by Spearman rank test (SRT) and MannWhitney U (MWU) test was used to delineate differences between glandular and extraglandular manifestations. Results: Increased SIGLEC1 expression was found in 60% of our cohort. In a subsequent analysis, SIGLEC1 was up-regulated in all patients with extraglandular manifestation, with an observed significant difference in SIGLEC1 expression (p=0.02, MWU) between glandular and extraglandular manifestation. SIGLEC1 expression correlated with the disease activity (p=0.002, r=0.6, SRT). Elevated levels of IP-10 levels were found in patients with pSS but did not show a difference between glandular and extraglandular manifestation nor did it correlate with the disease activity. Conclusions: SIGLEC1 is up-regulated in pSS patients with a known higher mortality and morbidity (5, 6), which therefore may be of value for a risk stratification, differential therapeutic approaches and guiding clinical decision making in pSS. References: Rönnblom L, Eloranta M-L. The interferon signature in autoimmune diseases. Curr Opin Rheumatol. 2013 Mar;25(2):248–53. Yao Y, Liu Z, Jallal B, Shen N, Rönnblom L. Type I interferons in Sjögren's syndrome. Autoimmun Rev. 2013 Mar;12(5):558–66. Kalunian KC, Merrill JT, Maciuca R, McBride JM, Townsend MJ, Wei X, et al. A Phase II study of the efficacy and safety of rontalizumab (rhuMAb interferon-α) in patients with systemic lupus erythematosus (ROSE). Ann Rheum Dis. 2015 Jun 2; Yao Y, Higgs BW, Morehouse C, de los Reyes M, Trigona W, Brohawn P, et al. Development of Potential Pharmacodynamic and Diagnostic Markers for Anti-IFN-α Monoclonal Antibody Trials in Systemic Lupus Erythematosus. Hum Genomics Proteomics HGP [Internet]. 2009 Nov 17 [cited 2016 Jan 27];2009. Available from: http://www.ncbi.nlm.nih.gov/pmc/articles/PMC2950308/ Singh AG, Singh S, Matteson EL. Rate, risk factors and causes of mortality in patients with Sjögren's syndrome: a systematic review and meta-analysis of cohort studies. Rheumatology. 2015 Sep 27;kev354. Skopouli FN, Dafni U, Ioannidis JPA, Moutsopoulos HM. Clinical evolution, and morbidity and mortalityof primary Sjögren's syndrome. Semin Arthritis Rheum. 2000 Apr;29(5):296–304. Disclosure of Interest: None declared